IMF Research Bulletin, March 2011. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2011)
The Q and A in this issue features seven questions on the role of precautionary savings in open economies (by Damiano Sandri); the research summaries are "The Macroeconomics of Aid (by Andrew Berg, Rafael Portillo, and Luis-Felipe Zanna) and "The Building Blocks to Measure Inflation" (by Mick Silver). The issue also lists the contents of the March 2011 issue of the IMF Economic Review, Volume 59 Number 1; visiting scholars at the IMF during January?March 2011; and recent IMF Working Papers and Staff Discussion Notes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet